ASR, Volume 18, n° 1, 2014 - Full Issue - Journal System (African Sociological Review, 2015)
Contents Editorial .................................................1 General Issues The Politics of ‘Hope and Despair’: Generational Dimensions to Igbo Nationalism in Post-War Nigeria Godwin Onuoha ........................................2 Religious Citizenship:The Case of the Globalised Khoja Iqbal S. Akhtar ...............................................27 African Agency: The Case Studies of the APRM and Africa’s Agenda Roseline Achieng ...........................................49 Research Papers Students perceiving risk: a qualitative assessment on three South African Campuses Asta Rau, Sarah Radloff, Jan Coetzee, Carlo Nardi, Ria smit & Sethulego Z. Matebesi .................65 Deprivation, HIV and AIDS in Northern Uganda Peter Rwagara Atekyereza ...........................................91 Le coupé décalé en Côte d’Ivoire : Sens et enjeux d’un succès musical Franck Gawa ......................................................112 An Investigation into the Factors impacting on Exports from South Africa to the Southern Africa Development Community (SADC) Collin Fish, Chris Adendorff and Kobus Jonker ..............................127 Book Review Agony in Nation-State Building. Review of Citizenship between Empire and Nation: Rethinking France and French Africa 1945-1960, Frederick Cooper Olajide Oloyede .................................................149